Oral Supplementation of Lead-Intolerant Intestinal Microbes Protects Against Lead (Pb) Toxicity in Mice - Zhai, Qixiao; Qu, Dingwu; Feng, Saisai; Yu, Yaqi; Yu, Leilei; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Chen, Wei (Frontiers in Microbiology, 2020)
Oral exposure to the heavy metal lead (Pb) causes various dysfunctions in animals. However, the influence of gut bacteria on Pb absorption, bioaccumulation and excretion is largely unknown. In this study we use a mouse model to investigate the relationship between gut microbiota, Pb-intolerant intestinal microbes and Pb toxicity. First, mice were treated with a broad-spectrum antibiotic cocktail to deplete their gut microbiota, and were then acutely and orally exposed to Pb at 1304 mg/kg for 3 days. Compared to the control mice, antibiotic-treated mice had increased Pb concentrations in the blood and primary organs and decreased Pb fecal concentrations, suggesting that gut microbiota limited the Pb burden that developed from acute oral Pb exposure. Next, three Pb-sensitive gut microbes, A. muciniphila, F. prausnitzii and O. ruminantium, were orally administered to mice, and their effects against Pb toxicity were evaluated. F. prausnitzii and O. ruminantium significantly decreased Pb concentrations in blood and primary tissues, upregulated tight junction (TJ) protein expression and the production of short-chain fatty acids (SCFA) by colonic microbiota, and also showed protective effects on liver and kidney toxicity. These results indicate the potential for reducing Pb toxicity by the modulation of gut microbiota.